2021
DOI: 10.3390/curroncol28010068
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Up-Front Minimally Invasive Esophagectomy versus Open Esophagectomy on Quality of Life for Esophageal Squamous Cell Cancer

Abstract: This study investigates whether minimally invasive esophagectomy (MIE) is a safe and effective way for patients with resectable esophageal cancer by comparing the short-term quality of life (QOL) after minimally invasive esophagectomy and open esophagectomy (OE). A total number of 104 patients who underwent esophagectomy from January 2013 to March 2014 were enrolled in this study. These patients were divided into two groups (MIE and OE group). Three scoring scales of quality of life were used to evaluate QOL b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Thus, open or hybrid surgical access, high and ECOG scores, (neo)adjuvant treatment, ICU readmission, and SCC predicted impaired functional outcome. Hence, our results confirm the findings of others that open access surgery leads to worse functional outcomes [13,38]. Because long-term oncologic outcomes after open and minimally invasive procedures are equivalent [39], our results underscore the importance of less invasive surgical procedures in patients undergoing esophagectomy.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, open or hybrid surgical access, high and ECOG scores, (neo)adjuvant treatment, ICU readmission, and SCC predicted impaired functional outcome. Hence, our results confirm the findings of others that open access surgery leads to worse functional outcomes [13,38]. Because long-term oncologic outcomes after open and minimally invasive procedures are equivalent [39], our results underscore the importance of less invasive surgical procedures in patients undergoing esophagectomy.…”
Section: Discussionsupporting
confidence: 89%
“…When performing esophagectomy, surgeons often face a dilemma in choosing between the latest Minimally Invasive Esophagectomy (MIE) and conventional surgery. Selecting the most HRQL-compatible surgical method is a complex process, as six recent original research studies have shown a direct correlation between MIE and poor postoperative HRQL [ 40 ]. Specifically, overall function worsened and dyspnea, pain, fatigue, insomnia, constipation, diarrhea, cough, and speech problems persisted for six months after MIE.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, overall function worsened and dyspnea, pain, fatigue, insomnia, constipation, diarrhea, cough, and speech problems persisted for six months after MIE. Speech problems and constipation persisted for 12 months and insomnia persisted for longer than 12 months [ 40 ]. Consequently, MIE and traditional surgery techniques have similar oncological outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation